Heterogeneous catalytic oxidation of R-(+)-limonene on Jacobsen type catalysts - Cubillos Lobo, Jairo Antonio (2014)
The development of heterogeneous catalytic processes is highly desirable in order to overcome somedrawbacks of homogeneous catalysts, such as the separation and recycling of these catalysts. In this work,we report that Jacobsen type catalysts are efficient and selective for the oxidation of R-(+)-limonene to itscorresponding diepoxides using in situ generated dimethyldioxirane (DMD) as oxidant. It was demonstratedthat the solid NaHCO3 addition to the initial reaction mixture, improves the catalytic activity. Additionally,catalyst samples can be recovered and reused at least twice without significant loss of its initial catalyticactivity.